PENERAPAN KOMUNIKASI INTERNAL PEGAWAI DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KOTA DENPASAR - Prabawa, I Ketut Indra; Paramarta, Wayan Arya (ANALISIS, 2023)
This research was conducted at the Community and Village Empowerment Office of Denpasar City. Research using qualitative methods. The purpose of this study was to determine the application and constraints of internal communication in the employee environment. This research focused on the application of internal communication in the Community and Village Empowerment Office of Denpasar City. This study uses primary data and secondary data. Primary data can be obtained by conducting interviews with informants, while secondary data is in the form of books containing theories and scientific journals that support research. The subjects in this study were employees of the Community and Village Empowerment Office of Denpasar City. The object of this study is the application of internal communication observation techniques, interviews, and documentation studies carried out by researchers to collect data. The results showed that internal communication between contract employees and superiors is also good, superiors who are civil servants consider contract employees as their colleagues, not consider them as subordinates who can be treated at will. Any obstacles in activities such as events that are scheduled from the scheduled hours there is a notification via WhatsApp Group but sometimes it is slow but the coordination is still managed properly the existing one is given notice so that all employees know it and a meeting is held to find solutions to problems and obstacles